2021
DOI: 10.1038/s41598-020-79325-8
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide hydrogel based 3D printed tumor models for chemotherapeutic drug screening

Abstract: A series of stable and ready-to-use bioinks have been developed based on the xeno-free and tunable hydrogel (VitroGel) system. Cell laden scaffold fabrication with optimized polysaccharide-based inks demonstrated that Ink H4 and RGD modified Ink H4-RGD had excellent rheological properties. Both bioinks were printable with 25–40 kPa extrusion pressure, showed 90% cell viability, shear-thinning and rapid shear recovery properties making them feasible for extrusion bioprinting without UV curing or temperature adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 97 publications
1
39
0
Order By: Relevance
“…Because of these multiple limitations of Matrigel as an ECM material, recent studies have analyzed alternative natural and synthetic hydrogels for different tissue culture applications ( Aisenbrey and Murphy, 2020 ; Kaur et al, 2021 ). In this work, we used a commercially available synthetic hydrogel, VitroGel ® ORGANOID 3 (V-ORG-3) ( Gebeyehu et al, 2021 ), which sustained HGO viability and growth while eliminating the batch-to-batch variation of Matrigel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of these multiple limitations of Matrigel as an ECM material, recent studies have analyzed alternative natural and synthetic hydrogels for different tissue culture applications ( Aisenbrey and Murphy, 2020 ; Kaur et al, 2021 ). In this work, we used a commercially available synthetic hydrogel, VitroGel ® ORGANOID 3 (V-ORG-3) ( Gebeyehu et al, 2021 ), which sustained HGO viability and growth while eliminating the batch-to-batch variation of Matrigel.…”
Section: Discussionmentioning
confidence: 99%
“…We used Matrigel (#354234, Corning, Corning, NY), rat tail collagen type I (#354-236, Corning, Bedford, MA, United States) and commercially available synthetic hydrogels, VitroGel ® ORGANOID 1-4 (#VHM04-K, TheWell Bioscience, NJ) as extracellular matrix materials. VitroGels ® are xeno-free polysaccharide-based hydrogels designed for 3-D tissue cultures that have been used in a number of cancer studies (Pang et al, 2019;Haruna and Huang, 2020;Gebeyehu et al, 2021;Wang et al, 2021). The VitroGel ® ORGANOID (V-ORG) Discovery Kit includes four types of organoid hydrogels (V-ORG-1-4) which contain proprietary formulations of various bio-functional ligands and which have different mechanical strengths and degradability to fulfill the needs of different organoid culture conditions.…”
Section: Extracellular Matrix Materialsmentioning
confidence: 99%
“…This is further supported by a cell uptake study, which showed that Tel pre-treatment significantly increased the uptake of FITC in 3D spheroids when compared to free FITC stained 3D spheroids as analyzed by flow cytometry. Decreased diffusion of chemotherapeutics through the spheroids contribute to resistance in 3D spheroid cultures, and tumor penetration remains a vital barrier inhibiting treatment response (52).…”
Section: Discussionmentioning
confidence: 99%
“…These models showed a drug response to cisplatin similar to the in vivo model, thus supporting the use of 3D printing for drug testing. This possibility was also confirmed in other types of cancers, such as cervical [177], brain [60,178], lung [179], and bladder [179,180]. The quick rising of novel bioprinted models of several types of cancer for drug screening and personalized medicine approaches, as well as the increasing trend of publications on bone models for oncology (Figure 3), clearly indicates that numerous studies will be published in the upcoming years for bone tumors as well.…”
Section: D-bioprinted Models Of Bone Cancersmentioning
confidence: 70%